2021
DOI: 10.1152/jn.00317.2019
|View full text |Cite
|
Sign up to set email alerts
|

Interjoint coupling of position sense reflects sensory contributions of biarticular muscles

Abstract: Perception of limb position and motion combines sensory information from spindles in muscles that span one joint (monoarticulars) and two joints (biarticulars). This anatomical organization should create interactions in estimating limb position. We developed two models, one with only monoarticulars (MO Model) and one with monoarticulars and biarticulars (MB Model), to explore how biarticulars influence estimates of arm position in hand (x,y) and joint (shoulder,elbow) coordinates. In hand coordinates, both mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In the research conducted by Roy et al resistance and motor control exercises improved shoulder function in people with SIS. Due to the effect on the muscles, especially in active motions, resistance exercises stimulate the muscular proprioception receptor [31]. When muscles are stretched in motorcycles, the muscle spindle stimulation rate becomes more than the position in which muscles are short, and this has a close relationship with accuracy and awareness of joint position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research conducted by Roy et al resistance and motor control exercises improved shoulder function in people with SIS. Due to the effect on the muscles, especially in active motions, resistance exercises stimulate the muscular proprioception receptor [31]. When muscles are stretched in motorcycles, the muscle spindle stimulation rate becomes more than the position in which muscles are short, and this has a close relationship with accuracy and awareness of joint position.…”
Section: Discussionmentioning
confidence: 99%
“…CKC exercises work on more than one muscle group and several joints simultaneously. Research has indicated that the CKC exercises cause more co-contractions in the lower limbs and increase the joint's stability compared to the OKC [31] since CKC exercises cause more co-contraction and improve joint stability in the upper limbs [33,34]. Lin et al (2007) argued that CKC exercises increased the activity of muscle spindles [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that biarticular muscles play a significant role in the coordination tasks of this group of movements [9], and impaired proprioception leads to deficits in interjoint coordination [10,11]. Describing the target movements of this group, N.A.…”
Section: Parametermentioning
confidence: 99%
“…Information concerning muscle forces and interaction forces stems from the detection of GTOs in the muscle (Crago et al, 1982; Jami, 1992; McCloskey, 1978; Onneweer et al, 2013; Proske & Gandevia, 2012;). GTOs provide a direct means of quantifying tendon strain, hence facilitating the elucidation of alterations in tendon force across different load conditions and enabling calculations of the length of the muscle‐tendon complex (Herter et al, 2021). Previous studies have found a linear correlation between the force produced by a muscle and the discharge rate of GTOs nearby (Crago et al, 1982).…”
Section: Discussionmentioning
confidence: 99%